The fall of the European public media revenues and audience (2010-2018) - Gesto-Louro, Alejandro (2020)
This article analyzes the negative evolution of the revenues of the European public media and the audience of its television channels between 2010 and 2018. The financial and share data –mainly obtained from the EAO– have been contrasted, at a quantitative level, with homogenizing economic indicators such as PPP; and have been grouped around the models proposed by Hallin and Mancini (2004, 2008, 2013). At a qualitative level, with the interviews of two academics –Tiziano Bonini (University of Siena) and Marko Ala-Fossi (University of Tampere)– and Mika Ojamies, director of international relations at YLE. However, despite the confirmation of this negative trend, there is no correlation between the decline in income and that of the audience. In any case, the Academy evidences the need to develop new financing systems that guarantee the budgetary stability of public media.